Post intubation tracheal stenosis in children - Marco Caruselli; Mirco Amici; Dario Galante; Olivier Paut; Giovanni De Francisci; Laura Carboni (MDPI AG, 2014)
Many authors have reported that tracheal stenosis is a complication that can follow tracheal intubation in both adults and children. The symptoms, when they do appear, can be confused with asthma, with subsequent treatment providing only mild and inconsistent relief. We report here the case of an 8 year old girl admitted to our hospital for whooping cough that was not responding to therapy.